PENGARUH INDEPENDENSI DAN KOMPETENSI TERHADAP KUALITAS AUDIT: (STUDI EMPIRIS PADA INSPEKTORAT SE PROVINSI RIAU) - Muhammad Fahdi (VALUTA, 2018)
This research aims to examine the effect of independence and competence on audit quality in the Inspectorate throughout Riau Province. The research was conducted on 66 civil servants in the examination section of the inspectorate in Riau Province. The participation rate of respondents was 68% (45 people). The analytical tool used is multiple regression of SPSS version 21. Tests conducted include testing validity and reliability, testing data normality and classical assumptions, coefficient of determination, and testing the research hypothesis. The results of the research show that the higher the competence, the higher the quality of audit. Meanwhile, independence does not have a positive and significant effect on audit quality. The coefficient of determination is 63.2%, which is still 32.8% explained by other factors not included in this research.